CO2 benefit from the increasing percentage of diesel passenger cars in Switzerland - Zervas, Efthimios; Bikas, Georgios; Zachariadis, Theodoros (My University, 2009)
One efficient way to decrease CO2 emissions is to replace gasoline passenger cars by diesel cars. The paper examines the benefit of CO2 emissions in the case of an increased diesel penetration in Switzerland, according to several scenarios assuming different future passenger car registrations and fuel consumption. The results show that a significant CO2 benefit can be achieved if a diesel penetration of more than 30% or 50% occurs. Future CO2 emissions from the transport sector can be partially controlled with increased diesel car sales, improved fuel consumption and replacement of heavy cars by lighter ones.
Keywords: Carbon dioxide; Diesel; Exhaust emissions; Fuel; Gasoline; Passenger cars; Switzerland